Altered proteolytic activity and expression of MMPs and aggrecanases and their inhibitors in Kashin–Beck disease. Issue 1 (26th September 2014) - Chen, Jinghong; Luo, Mingxiu; Wang, Wei; Zhang, Zentie; He, Ying; Duance, Victor C.; Hughes, Clare E.; Caterson, Bruce; Cao, Junling
Abstract Kashin–Beck disease (KBD) is a chronic, deforming endemic osteoarticular disease with altered metabolism of the cartilage matrix. Matrix metalloproteinases (MMPs), aggrecanases (ATAMTSs), and their inhibitors (TIMPs) play important roles in cartilage formation and matrix degradation. This study investigated these proteases and inhibitors in young KBD cartilage. The percentages of chondrocytes staining for MMP‐1/‐13 and MMP‐generated DIPEN neoepitope, aggrecanase‐generated ITEGE neoepitope in aggrecan in KBD patients were significantly higher than in controls. However, TIMP‐1 was significantly less numerous than in controls in the superficial and middle zones of KBD samples, the percentage of chondrocytes staining for the TIMP‐2 was significantly higher than in controls. Staining for MMP‐1/‐13 and, TIMP‐1/‐2 in KBD patients was prominent in the superficial zone and the middle zone of articular cartilage. Staining for ITEGE and DIPEN neoepitopes in KBD samples was prominent in the superficial zone and the middle zone of articular cartilage. The strongest staining for the MMP and aggrecanase‐generated neoepitopes was adjacent to areas of chondronecrosis. These results indicated that KBD cartilage destruction depends on collagen‐ and aggrecan‐degrading proteases such as collagenases (MMP‐1/‐13), as well as aggrecanases. Increased TIMP‐2 level adjacent to necrotic areas suggest that attempted repair mechanism are also activated. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:47–55, 2015.